2010
DOI: 10.1186/1743-422x-7-45
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein upregulates HSP90alpha expression via activation of c-Myc in human hepatocarcinoma cell line, HepG2

Abstract: BackgroundThe Hepatitis B Virus X protein (HBx) plays a major role in hepatocellular carcinoma (HCC) development, however, its contribution to tumor invasion and metastasis has not been established so far. Heat shock protein 90 alpha (HSP90alpha) isoform is an ATP-dependent molecular chaperone that maintains the active conformation of client oncoproteins in cancer cells, which is abundantly expressed in HCC, especially in hepatitis B virus (HBV)-related tumors, might be involved in tumor progression.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
1
27
1
1
Order By: Relevance
“…Lee [41]. As HBx is known to induce c-Myc expression [42], the observed downregulation of p53 in the present study might be due to increased binding of Myc to the p53 promoter. HBx has a controversial role in modulation of apoptosis: some studies have showed proapoptotic effects [43][44][45][46][47], while others have assigned an anti-apoptotic effect with a role in HCC [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 71%
“…Lee [41]. As HBx is known to induce c-Myc expression [42], the observed downregulation of p53 in the present study might be due to increased binding of Myc to the p53 promoter. HBx has a controversial role in modulation of apoptosis: some studies have showed proapoptotic effects [43][44][45][46][47], while others have assigned an anti-apoptotic effect with a role in HCC [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 71%
“…Association of HBV with liver cancer is well established, estimated to cause over a million deaths annually (Anzola 2004). HBV integrates its DNA within hepatocytes, enabling production of an oncogenic protein, HBx (Li et al 2010). The mechanisms by which this protein promotes carcinogenesis are manifold, with HBx described as a multifunctional factor able to inhibit a range of DNA repair and apoptotic mechanisms while upregulating growth factors (Zhang et al 2006).…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Firstly, several studies have uncovered various pathways which may be implicated in the increased motility of tumor cells, such as changes in the expression of proteins that may be involved in cell migration and decreased focal adhesion (e.g., upregulation of proteins such as MACF1, HMGB1, and Annexin A2 and downregulation of others such as Lamin A/C); activation of Rho GTPases and Rac1, with mutations at the sites of the proline-rich domain located in HBx; and upregulation of the expression of heat shock protein 90alpha (HSP90alpha) and c-met protein, as well as that of TANK-binding kinase-1 (TBK1), which induces the phosphorylation of NF-kappaB p65 at serine 536, at the transcriptional level [52,[76][77][78][79]. Secondly, the upregulation of inflammatory mediators by HBx is another pathway of interest.…”
Section: Trans-activating Mechanisms Of Hbxmentioning
confidence: 99%